THE UPTAKE ABILITY OF THE CLINOPTILOLITIC TUFFS OF SAMOS ISLAND, GREECE - Kantiranis, N.; Stamatakis, M.; Filippidis, A.; Squires, C. (Bulletin of the Geological Society of Greece, 2004)
The bulk mineralogy and uptake ability of four samples (SA1 to SA4) of clinoptilolite-bearing tuffs from Samos Island, Greece were investigated. The semi-quantitative mineralogical analyses of the samples were determined by powder-XRD (PXRD). The chemical composition of the samples analysed by Atomic Absorption Spectroscopy (AAS), reflected the bulk mineralogy of the samples. The semi-quantitative mineralogy of the samples was found to be in good agreement with their chemical compositions. The uptake ability was measured using the ammonium saturation method (AMAS). The samples consist of clinoptilolite (47-74 wt. %), micas (muscovite and/or illite) (4-13 wt. %) and smectite (2-13 wt. %) and have uptake abilities between 133 and 184 meq/100g. Such materials, especially the clinoptilolite-rich ones, could be used in a wide range and scale of agricultural, aquacultural, industrial and environmental applications.